Paisagem e percepção ambiental no município de Itirapina/SP - Nabhan, Natália [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The present study intends through the Humanistic Cultural Geography, to explore the interface society and nature, from the point of view of the study of Landscape. In this work, will be made the survey of the perception of the students of Itirapina, in relation to their knowledge about the Ecological Station and Experimental Station of the municipality. Other specific objectives were the creation of an environmental primer for the population, according to the needs pointed out by the study and the mapping of the current land use. The methodology included bibliographic review, fieldwork, questionnaire application and mapping methodology. Among the results of the questionnaires, most students said they have heard of the two protected areas and consider their protection important. The vegetation identified was pinus (33%), eucalyptus (22%), riparian forest (21%) and cerrado (10%). However, there was some confusion as to which was belonging to the ecological station and to which it is present in the experimental station. As for the preference of the images, the majority preferred the images of the resort (56%), pinus (31%) and finally the cerrado with 13%. For this reason, it was noted the low value of the cerrado and this fragility a booklet was made explaining, among other subjects, the importance of the cerrado

O estudo apresentado pretende através da Geografia Humanística Cultural, explorar a interface sociedade e natureza, do ponto de vista do estudo da Paisagem. Neste trabalho, será feito o levantamento da percepção dos estudantes de Itirapina, em relação ao conhecimento dos mesmos sobre a Estação Ecológica e Estação Experimental do município. Outros objetivos específicos foram à confecção de uma cartilha ambiental para a população, conforme as necessidades apontadas pelo estudo e o mapeamento do uso do solo atual. A metodologia abrangeu revisão bibliográfica, trabalhos de campo, aplicação de questionário e metodologia de mapeamentos. Dentre os resultados dos questionários, a maioria dos estudantes disse que já ouviu falar das duas áreas protegidas e considera importante sua proteção. A vegetação identificada foi pinus (33%), eucalipto (22%) mata ciliar (21%) e cerrado (10%). Todavia, houve um pouco de confusão quanto à qual era pertencente à estação ecológica e à qual é presente na estação experimental. Quanto a preferência das imagens, a maioria preferiu as imagens do resort (56%), pinus (31%) e por último o cerrado com 13%. Por essa questão, notou-se a baixa valorização do cerrado e dessa fragilidade realizou-se uma cartilha explicando dentre outros assuntos, a importância do cerrado
Keywords: Paisagens; Avaliação paisagística; Áreas protegidas; Itirapina (SP)